2014
DOI: 10.4103/2153-3539.129443
|View full text |Cite
|
Sign up to set email alerts
|

Pocket pathologist: A mobile application for rapid diagnostic surgical pathology consultation

Abstract: Introduction:Telepathology allows the digital transmission of images for rapid access to pathology experts. Recent technologic advances in smartphones have allowed them to be used to acquire and transmit digital images of the glass slide, representing cost savings and efficiency gains over traditional forms of telepathology. We report our experience with developing an iPhone application (App - Pocket Pathologist) to facilitate rapid diagnostic pathology teleconsultation utilizing a smartphone.Materials and Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Static image telepathology has been described as a low-cost solution for providing second opinions from experts across the world. 33 As Internet access becomes more readily available, social media sites could be repurposed as a portal through which low-cost microscopic imaging systems, such as via smartphone microscopy (either free hand or using an adapter) technique, [34][35][36][37][38][39][40][41] more sophisticated low-resource whole slide imaging systems, 42 and low-cost telepathology applications, 43 could create another avenue for consultation around the world.…”
Section: Discussionmentioning
confidence: 99%
“…Static image telepathology has been described as a low-cost solution for providing second opinions from experts across the world. 33 As Internet access becomes more readily available, social media sites could be repurposed as a portal through which low-cost microscopic imaging systems, such as via smartphone microscopy (either free hand or using an adapter) technique, [34][35][36][37][38][39][40][41] more sophisticated low-resource whole slide imaging systems, 42 and low-cost telepathology applications, 43 could create another avenue for consultation around the world.…”
Section: Discussionmentioning
confidence: 99%
“…Use of LISs on other client devices, such as tablets and smartphones, is emerging as well. 3,4 LISs require the use of networking technologies for connections among the LIS infrastructure components. Networks consist of physical media and related engineering software that together enable electronic data exchange.…”
Section: Laboratory Information System Infrastructurementioning
confidence: 99%
“…Although focusing primarily on the use of adapters, a comparison of system features in Table 1 from their article included the hands-free technique that we first described. 5 Also in 2014, Hartman et al 6 from the same group at the UPMC reported their revolutionary application (app) available on Apple's iOS system that enabled users to capture images on their smartphone and upload them directly through the app to the UPMC's website for a consultation through the Department of Pathology. 6 The combination of online consultation with direct integration of an iOS app set a new precedent for using microscopic images captured with a smartphone camera for second opinion consultations.…”
Section: To the Editormentioning
confidence: 99%